Effect of Combined Oral Contraceptive on Flap Surgery in Female Rat Model - Abdulkadir Calavul; Burhan Özalp; Serdar Menekşe (Revista Científica)
Combined oral contraceptives (COCs) are said to have a negative effect on flap surgery's outcomes due to their adverse effects on tissue perfusion, managing inflammation, and oxidative stress. This study aimed to investigate the effects of COCs use on flap survival in a female rat model. In this randomized controlled experimental study, a total of 20 female Wistar Albino rats were divided into control and COC groups (n=10/group). The COC group received Desolett® (Desogestrel 0.15 mg, Ethinyl estradiol 0.03 mg) orogastrically for three weeks. The McFarlane flap model was surgically implemented, and flap survival was evaluated using digital planimetry. Histopathological and biochemical analyses were performed during the postoperative period. The flap survival rate in the COC group was significantly lower compared to the control group (74.4 vs 83.7%, P=0.012). Furthermore, the COC group demonstrated a higher necrotic area ratio (25.7 vs 18.4%, P=0.015) and more severe inflammatory cell infiltration (2.4 ± 0.5 vs 1.8 ± 0.4, P=0.011). Biochemical analyses revealed higher malondialdehyde (MDA) levels (4.86 ± 0.72 vs 3.24 ± 0.58 nmol/mg, P=0.008) and lower superoxide dismutase (SOD) activity (14.2 ± 2.1 vs 18.5 ± 2.4 U/mg, P=0.012) in the COC group. Using COCs reduces the chances of a successful flap surgery and promotes the chances of complications arising owing to oxidative stress, inflammation and impairment of tissue perfusion. These observations merit caution while planning flap surgery for COCs users and a recommendation for a brief halt in the usage of COCs should be made. The results underscore the importance of understanding the potential implications of COCs use in surgical planning and postoperative care management.